2017
DOI: 10.1259/dmfr.20160281
|View full text |Cite
|
Sign up to set email alerts
|

Image findings of bisphosphonate related osteonecrosis of jaws comparing with osteoradionecrosis

Abstract: Image findings of BRONJ were characterized as a severe sclerotic change combined with osteolysis, sequestration, periosteal reaction and spread of soft tissue inflammation around the jaws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
0
18
0
4
Order By: Relevance
“…2 Despite histopathological and clinical similarities, the above-mentioned pathologies also exhibit very similar image characteristics. 7,8 Authors have presented a detailed image description comparing BRONJ and ORNJ from dental panoramic radiographs and computed tomography and have pointed out a number of similarities between the two pathologies, such as osteolysis, osteosclerosis, sequestration, and dissemination of soft tissue inflammation, emphasizing only two main differences between them, namely predominant osteolysis in ORNJ and osteosclerosis in MRONJ cases. 7 There are few pathological studies comparing OMJ, MRONJ, and ORNJ in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Despite histopathological and clinical similarities, the above-mentioned pathologies also exhibit very similar image characteristics. 7,8 Authors have presented a detailed image description comparing BRONJ and ORNJ from dental panoramic radiographs and computed tomography and have pointed out a number of similarities between the two pathologies, such as osteolysis, osteosclerosis, sequestration, and dissemination of soft tissue inflammation, emphasizing only two main differences between them, namely predominant osteolysis in ORNJ and osteosclerosis in MRONJ cases. 7 There are few pathological studies comparing OMJ, MRONJ, and ORNJ in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Authors have presented a detailed image description comparing BRONJ and ORNJ from dental panoramic radiographs and computed tomography and have pointed out a number of similarities between the two pathologies, such as osteolysis, osteosclerosis, sequestration, and dissemination of soft tissue inflammation, emphasizing only two main differences between them, namely predominant osteolysis in ORNJ and osteosclerosis in MRONJ cases. 7 There are few pathological studies comparing OMJ, MRONJ, and ORNJ in the literature. 1,2,3,9 Therefore, the present study aimed to compare the histopathological features of these bone diseases in order to detect some common or prevalent aspects.…”
Section: Introductionmentioning
confidence: 99%
“…2). Важнейшими факторами развития осложнений в ЧЛО является зависимость от разовых и суммар-ных доз противоопухолевых препаратов, механиз-ма действия, и, главное, режимов их введения [16,18,22].…”
Section: влияние химиотерапевтического лечения на стоматологический сunclassified
“…According to Barragan et al,22 the PR revealed the osteolytic lesions of osteonecrosis associated with the use of bisphosphonates, but it was neither able to show the real total extent of the lesion nor more detailed information of the area of bone sequestration as shown by the three-dimensional examinations 22. At a later stage, MRONJ may behave in a destructive manner, leading to areas of pathological fractures and cortical ruptures, but the PR examination may not reveal the lines of bone fracture and will not be able to reveal the involvement of the lingual and buccal cortices, making it impossible to correctly analyze the behavior of the lesion in relationship with adjacent structures 23. Radiographic findings of MRONJ found in PR are nonspecific, being more evident when a decrease of 30-50% in bone mineral density occurs, that is, when bone involvement is more significant due to buccal / lingual cortical thickness.…”
mentioning
confidence: 99%
“…24 As well as PR, it is also possible to assess areas that are compatible with bone sclerosis, hypodense regions compatible with osteolysis, thickening of the lamina dura, periosteal reaction, bone sequestration and mandible fractures. 17 Obinata et al assessed the imaging features present in the MRONJ by comparing helical computed tomography (CT) and PR, and they foundthat CT provided more detailed information of osteolysis, osteosclerosis, bone sequestration, and periosteal reactions than in PR 23.…”
mentioning
confidence: 99%